EVALUATION OF THE EFFECT OF LAPAROSCOPIC LONGITUDINAL GASTOECTOMY PRACTICE ON CARBOHYDRATE METABOLISM DISORDERS IN MORBIDLY OBESE PATIENTS - Oktyabr R. Teshaev; Alijon S. Muradov (Central Asian Journal of Medicine, 2023)
Objective is to study and evaluate carbohydrate metabolism after laparoscopic longitudinal gastroectomy (LLG) in morbidly obese patients. Materials and methods: 231 bariatric and metabolic operations were performed in our clinical bases from 2016 to 2022, of which 82 were MGSh and 149 were LLG. Result: In our clinic, the effect of LLG practice on carbohydrate metabolism was studied and evaluated before practice and 6 months after practice. Among 11 patients with type 2 diabetes in our observation groups, clinical improvement of disease symptoms was observed in 3(27%) and complete remission in 8(73%) patients after LLG procedure. It is noteworthy that there were no patients whose clinical course of the disease remained unchanged after the operation. Conclusion: As a result of the corrective effect of laparoscopic longitudinal gastroectomy on existing metabolic indicators in patients suffering from morbid obesity, it improves the course of early postoperative period and concomitant diseases in patients, and has a positive effect on the clinical course of not only prediabetes, but also diabetes.